Compressive Strength of Coconut Fiber Concrete Using Sea Water as a Solvent - Arman Hidayat; Mursalim Ninoy La Ola; Muhammad Buttomi Masgode; Al Tafakur La Ode (JOURNAL OF CIVIL ENGINEERING BUILDING AND TRANSPORTATION, 2023)
Concrete is a mixture of Portland cement or other hydraulic cement, fine aggregate, coarse aggregate and water or without additives to form a solid mass. The researcher aims to find out how much influence the compressive strength of coco fiber concrete has with sea water as a solvent. The method used in this study was an experimental method, cylindrical concrete was printed with a size of 15x30 cm by adding coconut fiber to the concrete mixture with fc' quality of 22.5 MPa and as a comparison the researchers made samples of coconut fiber concrete with fresh water as a solvent. The results of this study with the addition of 1% fiber by weight of cement at the age of 3 days the compressive test reached 10.02 MPa for fresh water concrete and 6.51 MPa for sea water coir concrete. At the age of 7 days, fresh water concrete was 15.76 MPa, while coconut coir concrete was 7.42 MPa. For 28 days the fresh water concrete is 23.78 MPa, while the sea water coconut coir concrete is 14.72 MPa. The conclusion obtained in this research is that the use of sea water as a solvent in coconut coir concrete has decreased in strength by 23.53% compared to coconut coir concrete with fresh water as a solvent for 28 days of age.